Reduction Of Bacteria Cells Viability In Injection Water By Using Ammonium Chloride - Zulkifliani Zulkifliani; Usman Usman (Testing Center for Oil and Gas LEMIGAS, 2011)
Ammonium chloride is one of the biocides used to reduce viability of bacterial cells inÂ produced water from oil wells that will be applied as injection water. The advantage of this biocide is having high epication penetrate the cell wall, causing death of bacteria cells (bacteriocidal). Tests for antibacterial activity was done by using the API RP-38 method by adding ammonium chloride into the produced water to obtain the final concentrations of 4, 8, 16, 32, 64, and 128 mg/L. Laboratory test results showed that giving ammonium chloride at a concentration of 64 mg/L can significantly reduced the viability of bacterial cells, including groups of aerobic and anaerobic bacteria.